Efficacy of Spironolactone Treatment in Murine Models of Cutaneous and Visceral Leishmaniasis - Andrade-Neto, Valter Viana; da Silva Pacheco, Juliana; Inácio, Job Domingos; Almeida-Amaral, Elmo Eduardo; Torres-Santos, Eduardo Caio; Cunha-Junior, Edezio Ferreira (Frontiers in Pharmacology, 2021)
Translational studies involving the reuse and association of drugs are approaches that can result in higher success rates in the discovery and development of drugs for serious public health problems, including leishmaniasis. If we consider the number of pathogenic species in relation to therapeutic options, this arsenal is still small, and each drug possesses a disadvantage in terms of toxicity, efficacy, price, or treatment regimen. In the search for new drugs, we performed a drug screening of L. amazonensis promastigotes and intracellular amastigotes of fifty available drugs belonging to several classes according to their pharmacophoric group. Spironolactone, a potassium-sparing diuretic, proved to be the most promising drug candidate. After demonstrating the in vitro antileishmanial activity, we evaluated the efficacy on a murine experimental model with L. amazonensis and L. infantum. The treatment controlled the cutaneous lesion and reduced the parasite burden of L. amazonensis significantly, as effectively as meglumine antimoniate. The treatment of experimental visceral leishmaniasis was effective in reducing the parasite load on the main affected organs (spleen and liver) via high doses of spironolactone. The association between spironolactone and meglumine antimoniate promoted better control of the parasite load in the spleen and liver compared to the group treated with meglumine antimoniate alone. These results reveal a possible benefit of the concomitant use of spironolactone and meglumine antimoniate that should be studied more in depth for the future possibility of repositioning for leishmaniasis co-therapy.